1993
DOI: 10.1164/ajrccm/147.2.462
|View full text |Cite
|
Sign up to set email alerts
|

An Amphipathic α-Helical Decapeptide in Phosphatidylcholine Is an Effective Synthetic Lung Surfactant

Abstract: An idealized model amphipathic alpha-helical decapeptide was synthesized and tested for efficacy as a totally synthetic lung surfactant in simple mixtures with dipalmitoylphosphatidylcholine (DPPC). Quasi-static lung compliance was restored to 92 +/- 3% of the unlavaged value at a pressure of 5 cm H2O in an in vitro lavaged rat lung model. A sustained improvement in gas exchange was also observed when guinea pigs were treated with the synthetic lung surfactant in an in vivo lavaged lung model. DPPC/peptide mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Admixtures of DPPC and variable proportions of these simple peptides had enough surface activity to mimic pulmonary surfactant in animal models of surfactant deficiency [89][90][91][92]. This evidence provides support for the idea that a clinical surfactant could, in principle, be produced by a proper combination of lipids and synthetic peptides.…”
supporting
confidence: 52%
“…Admixtures of DPPC and variable proportions of these simple peptides had enough surface activity to mimic pulmonary surfactant in animal models of surfactant deficiency [89][90][91][92]. This evidence provides support for the idea that a clinical surfactant could, in principle, be produced by a proper combination of lipids and synthetic peptides.…”
supporting
confidence: 52%
“…Several studies on synthetic peptides that exhibit surfactant activity in vitro have been reported (e.g. Baatz et al, 1991;Vincent et al, 1991;McLean et al, 1993;Johansson et al, 1995a;Lipp et al, 1996). It is however difficult to judge the pharmacological impact from such studies alone, since simple homopolymeric peptides also exhibit similar effects (Venkitaraman et al, 1990), and apparently few of these peptides possess significant effects in vivo.…”
Section: Structures Interactions and Dynamics In Relation To Functiomentioning
confidence: 99%
“…Also, synthetic peptides with simplified sequences designed to mimic specific parts of the SP-B polypeptide [258,260], and amphipathic α-helical peptides based on SP-A [261], exhibit some surface activity in combination with phospholipids. However, although encouraging, such results should perhaps be taken somewhat cautiously, since an amphipathic α-helical decapeptide with a sequence unrelated to SP-B [262], or simple amino acid homopolymers [263] combined with phospholipids also exhibit biophysical activities that are superior to phospholipids alone, but inferior to natural pulmonary surfactant.…”
Section: Functional Correlationsmentioning
confidence: 99%